Increasing Intelligent Systems’ Reliability by using Reconfiguration - Meyer, Tobias; Kessler, Jan Henning; Sextro, Walter; Trächtler, Ansgar (The Annual Reliability and Maintainability Symposium (RAMS))
Self-optimizing mechatronic systems allow the adaptation of the system’s behavior to the current situation. This can be used to actively adapt the behavior to the current degradation state of the system or of some of its components. To this end, the Multi-Level Dependability Concept has been developed. In this contribution, we show how the Multi-Level Dependability Concept has been applied to the active suspension module of an innovative rail-bound vehicle. For this module, the usage of control reconfiguration, which is a novel approach to exploit complex redundancy systems, is required. We show that by combining self-optimization with the possibilities given by control reconfiguration, the dependability of a complex mechatronic system can be greatly improved.

Performance Benchmarking for Designing Interaction Routines --- Managing Trade-offs in Service Co-creation with the Data Envelopment Analysis - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Peter Rauer, Hans (Proceedings of the European Research Conference on Information Systems (ECIS) 2013)

On the Design of IT Artifacts and the Emergence of Business Processes as Organizational Routines - Beverungen, Daniel (Proceedings of the 34th International Conference on Information Systems (ICIS))

Local e-Government Transformation --- An International Comparison - Dillon, S; Deakins, E; Beverungen, Daniel; Kohlborn, T; Hofmann, S; Räckers, M (WEBIST)

Old Blunders in New Media? How Local Governments Communicate with Citizens in Online Social Networks - Hofmann, Sara; Räckers, Michael; Beverungen, Daniel; Becker, Jörg (Proceedings of the 46$^{th}$ Hawaii International Conference on System Sciences (HICSS-46))

Capitalizing on Social Media Analysis --- Insights from an Online Review on Business Models - Malsbender, Andrea; Beverungen, Daniel; Voigt, Matthias; Becker, Jörg (Proceedings of the Americas Conference on Information Systems (AMCIS2013))

Much Ado about Nothing? Tracing the Progress of Innovations Borne on Enterprise Social Network Sites - Malsbender, Andrea; Recker, Jan; Kohlborn, Thomas; Beverungen, Daniel; Tanwer, Satya (Proceedings of the 34th International Conference on Information Systems (ICIS))

Digital Social Signal Processing --- Theoretical Underpinning and Research Agenda - Malsbender, Andrea; Voigt, Matthias; Beverungen, Daniel; Rosemann, Michael (Proceedings of the Pacific Asia Conference on Information Systems (PACIS))

Unravelling (E-)Government Channel Selection: A Quantitative Analysis of Individual Customer Preferences in Germany and Australia - Plattfaut, Ralf; Kohlborn, Thomas; Hofmann, Sara; Beverungen, Daniel; Niehaves, Björn; Räckers, Michael; Becker, Jörg (Proceedings of the 46th Hawaii International Conference on System Sciences)

Guidelines for Reporting Productivity Studies: A Review of the Reproducibility of DEA in the Service Sector - Becker, Jörg; Beverungen, Daniel; Breuker, Dominic; Dietrich, Hanns-Alexander; Peter Rauer, Hans (International Journal of Services and Operations Management)

Bridging the Gap Between Manufacturing and Service Through IT-Based Boundary Objects - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (IEEE Transactions on Engineering Management)

Designing Interaction Routines in Service Networks: A Modularity and Social Construction-Based Approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuß, Jens (Scandinavian Journal of Information Systems)

Augmenting Analytical CRM Strategies with Social BI - Beverungen, Daniel; Eggert, Mathias; Voigt, Matthias; Rosemann, Michael (International Journal of Business Intelligence Research (IJBIR))

What Makes Local Governments' Online Communications Successful? Insights from a Multi-Method Analysis of Facebook - Hofmann, Sara; Beverungen, Daniel; Räckers, Michael; Becker, Jörg (Government Information Quarterly)

Verwaltungsdienstleistungen für Personen mit eingeschränkter Mobilität: Von mobilen Bürgerdiensten zu E-Government? - Plattfaut, Ralf; Hofmann, Sara; Kohlborn, Thomas; Beverungen, Daniel; Räckers, Michael; Niehaves, Björn; Becker, Jörg (eGovernment Review)

Intuitive expertise: Theories and empirical evidence - Harteis, Christian; Billett, Stephen (Educational Research Review)

Learning Efficient Information Extraction on Heterogeneous Texts - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the Sixth International Joint Conference on Natural Language Processing)

Information Extraction as a Filtering Task - Wachsmuth, Henning; Stein, Benno; Engels, Gregor (Proceedings of the 22nd ACM International Conference on Conference on Information & Knowledge Management)

Automatic Pipeline Construction for Real-Time Annotation - Wachsmuth, Henning; Rose, Mirko; Engels, Gregor (14th International Conference on Intelligent Text Processing and Computational Linguistics)

Practical algorithms for clustering and modeling large data sets - Analysis and improvements - Kuntze, Daniel

An Approach for Determining Optimal Contrast in Visual Cryptography - Juhnke, Jakob; Lefmann, Hanno; Strehl, Volker

Improved Side Channel Attacks on Pairing Based Cryptography - Blömer, Johannes; Günther, Peter; Liske, Gennadij (Constructive Side-Channel Analysis and Secure Design)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (J. Cryptology)

Practical Signatures from Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Hong Seo, Jae; Striecks, Christoph (Advances in Cryptology - EUROCRYPT 2013, 32nd Annual International Conference on the Theory and Applications of Cryptographic Techniques, Athens, Greece, May 26-30, 2013. Proceedings)

One Bad Apple: Backwards Compatibility Attacks on State-of-the-Art Cryptography - Jager, Tibor; Paterson, Kenneth G.; Somorovsky, Juraj (20th Annual Network and Distributed System Security Symposium, NDSS 2013, San Diego, California, USA, February 24-27, 2013)

Bounded Model Checking of Graph Transformation Systems via SMT Solving - Isenberg, Tobias; Steenken, Dominik; Wehrheim, Heike (Formal Techniques for Distributed Systems - Joint IFIP WG 6.1 International Conference, {FMOODS/FORTE} 2013, Held as Part of the 8th International Federated Conference on Distributed Computing Techniques, DisCoTec 2013, Florence, Italy, June 3-5, 2013. Proceedings)

SPIN as a Linearizability Checker under Weak Memory Models - Travkin, Oleg; Mütze, Annika; Wehrheim, Heike (Hardware and Software: Verification and Testing - 9th International Haifa Verification Conference, HVC 2013, Haifa, Israel, November 5-7, 2013, Proceedings)

A High-Level Semantics for Program Execution under Total Store Order Memory - Dongol, Brijesh; Travkin, Oleg; Derrick, John; Wehrheim, Heike (Theoretical Aspects of Computing - ICTAC 2013 - 10th International Colloquium, Shanghai, China, September 4-6, 2013. Proceedings)

Temporal Reconfiguration Plans for Self-Adaptive Systems - Ziegert, Steffen; Wehrheim, Heike (Software Engineering 2013: Fachtagung des GI-Fachbereichs Softwaretechnik, 26. Februar - 2. März 2013 in Aachen)

Time trends in dietary fat intake in a sample of German children and adolescents between 2000 and 2010: not quantity, but quality is the issue - Libuda, Lars; Alexy, Ute; Kersting, Mathilde (British Journal of Nutrition)
Dietary fat intake in childhood may influence the risk for developing chronic diseases. The objective of the present study was to examine secular trends in the parameters of fat intake between 2000 and 2010 in a sample of German children and adolescents ( n 808) participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Dietary data from 4380 3 d weighed dietary records were analysed using repeated-measures regression to determine time trends in fat quantity, i.e. the intake of total fat, and in fat quality, i.e. the ratios of SFA, MUFA and PUFA. In young children (2–3 years) and in adolescents (13–18 years), total fat intake remained stable over time, but decreased by 0·08 % of total energy (%E) per year in 4–12-year-old children. In 2010, median fat intake was at the upper end of the recommendations. SFA intake decreased slightly in 2–3- and 4–12-year-old children by 0·09 and 0·05 %E per year, respectively. MUFA and PUFA intakes remained stable in all the age groups except in adolescents. Here, PUFA intake decreased initially, but increased between 2005 and 2010. In 2010, only between 3 and 18 % of the respective age groups had an intake of SFA or PUFA within the recommendations. In conclusion, fat quantity and quality did not change substantially between 2000 and 2010. Fat quality, in particular, needs to be improved, since a large percentage of our sample did not meet the recommended intakes for SFA and PUFA.

11. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Frequencies and demographic determinants of breastfeeding and DHA supplementation in a nationwide sample of mothers in Germany - Libuda, Lars; Stimming, Madlen; Mesch, Christina; Warschburger, Petra; Kalhoff, Hermann; Koletzko, Berthold Viktor; Kersting, Mathilde (European Journal of Nutrition)

Lunch at school, at home or elsewhere. Where do adolescents usually get it and what do they eat? Results of the HELENA Study - Müller, Katrin; Libuda, Lars; Diethelm, Katharina; Huybrechts, Inge; Moreno, Luis A.; Manios, Yannis; Mistura, Lorenza; Dallongeville, Jean; Kafatos, Anthony; González-Gross, Marcela; Cuenca-García, Magdalena; Sjöström, Michael; et al. (Appetite)

Effects of lunch on children’s short-term cognitive functioning: a randomized crossover study - Müller, K; Libuda, Lars; Gawehn, N; Drossard, C; Bolzenius, K; Kunz, C; Kersting, M (European Journal of Clinical Nutrition)

Approaches for an informational separation of powers in learning platforms - Keil, Reinhard; Winkelnkemper, Felix

„Do You Speak Usability?“ – Aktueller Stand des Glossars und des Curriculums für den „Certified Professional for Usability and User Experience (CPUX)“ der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter; Polkehn, Knut

Contextual tagging in the coactive knowledge organization - K {\ "u} hnel, Birger

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten

Computer science and education - A struggle for creative sovereignty in society? - Keil, Reinhard; Selke, Harald; Winkelnkemper, Felix (FIfF-Kommunikation)

Media contexts - context media - Keil, Reinhard

A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

A Crook is a Crook … But is He Still a Crook Abroad? - On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

A crook is a crook ... but is he still a crook abroad? On the effect of immigration on destination-country corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

Musical Variants in Encoding, Analysis and Visualization - Kepper, Johannes; Roland, Perry; Röwenstrunk, Daniel (Balisage: The Markup Conference 2013)

Bildung für nachhaltige Entwicklung. Den Alltag gestalten – Teilhabe ermöglichen. Verbraucherbildung als Aufgabe von Schule - Oepping, Anke; Schlegel-Matthies, Kirsten (Schule NRW. Amtsblatt des Ministeriums für Schule und Weiterbildung)

Ethik, Konsumentenverantwortung und Verbraucherbildung im Spannungsfeld - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Fachliche Betreuung des Schwerpunktthemas: Ethik – Konsum – Verbraucherbildung. - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Ernährungs- und Verbraucherbildung im Unterricht - Oepping, Anke; Schlegel-Matthies, Kirsten

Business Model Representations: A Cross-Disciplinary Review of the Pragmatic, Semantic and Syntactic Foundations of Existing Approaches - John, Thomas; Kundisch, Dennis (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

A Review of the Effects of Lunch: On Adults’ Short-term Cognitive Functioning - Müller, Katrin; Libuda, Lars; Terschlüsen, Anna Maria; Kersting, Mathilde (Canadian Journal of Dietetic Practice and Research)
Because of widespread irregular lunch consumption by both children and adults, information on the effects of lunch on short-term cognitive functioning is relevant to public health. In September 2012, a MEDLINE search was conducted for studies in which the effects of lunch on cognitive performance were examined. Eleven experimental studies published from 1981 to 1996 were found and evaluated; all involved adults. In three studies, the effects of lunch and lunch skipping were compared; the remaining studies involved a determination of the effects of lunch size and lunch composition. Results of studies in which lunch was compared with no lunch indicate that lunch leads to potential impairment of some aspects of cognitive functioning in the early afternoon. Lunch size may influence cognitive functioning, with impairment more likely to occur after a large lunch than a small lunch. Furthermore, in comparison with low-fat lunches, high-fat lunches seem to result in slower but more accurate responses to some cognitive tasks. However, these suggestions must be viewed with caution, as they are based on only a few studies and are not thoroughly supported by high-quality evidence. In addition, results obtained with adults are not applicable to children. Thus, the potential effects of lunch need further examination in children and adults.